2017
DOI: 10.1186/s13033-017-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Service user and care giver involvement in mental health system strengthening in Nepal: a qualitative study on barriers and facilitating factors

Abstract: BackgroundService user and caregiver involvement has become an increasingly common strategy to enhance mental health outcomes, and has been incorporated in the mental healthpolicies of many developed nations. However, this practice is non-existent or fragmented in low and middle income countries (LMICs). Instances of service user and caregiver involvement have been rising slowly in a few LMICs, but are rarely described in the literature. Very little is known about the context of user and caregiver participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 51 publications
7
60
0
Order By: Relevance
“…The poor representation of mental healthcare service users at the national consultation summit confirms other studies demonstrating limited service-user participation in policy development in low-and middle-income countries [10,44,45], and in South Africa in particular [23,46]. This study, as in other studies [47,48], showed that service-user involvement in the consultation summit was limited and somewhat tokenistic.…”
Section: Service-user Involvementsupporting
confidence: 83%
“…The poor representation of mental healthcare service users at the national consultation summit confirms other studies demonstrating limited service-user participation in policy development in low-and middle-income countries [10,44,45], and in South Africa in particular [23,46]. This study, as in other studies [47,48], showed that service-user involvement in the consultation summit was limited and somewhat tokenistic.…”
Section: Service-user Involvementsupporting
confidence: 83%
“…17,18 Despite the ubiquity of involvement rhetoric within policy and practice ideologies across the world, current evidence suggests implementation remains far from optimal and service user and carer isolation and dissatisfaction persist. 10,[19][20][21][22][23][24] In a recent commentary, it was argued that true collaboration between people with mental health diagnoses and researchers, policy makers and health professionals cannot happen in environments which continue to perpetuate hierarchies and power imbalances albeit in a less transparent form. 25 Often such imbalances are sustained by macro-level factors such as the legacy of prior mental health policy and historical practice, legal frameworks and organizational cultures often not targeted or considered by PPI interventions.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…• Development and adaptation of 27 modules on mental health systems for integration within Qualitative in-depth interviews were conducted at baseline to identify priority goals for service user and caregiver interventions and capacity-building needs (Samudre et al 2016;Abayneh et al 2017;Gurung et al 2017). Follow-up qualitative interviews are planned in order to explore perceptions of the impact of Emerald capacity-building upon service user and caregiver involvement in mental health system strengthening, the level of empowerment and mobilisation, the experience of participation in capacity-building, perceived limitations to the capacity-building approach and recommendations on how to improve capacity-building efforts.…”
Section: Emerald Evaluation Of Capacity-building For Service Users Anmentioning
confidence: 99%